NAMPT and NAPRT serum levels predict response to anti-TNF therapy in inflammatory bowel disease - Colombo, Giorgia; Caviglia, Gian Paolo; Ravera, Alberto; Tribocco, Elisa; Frara, Simone; Rosso, Chiara; Travelli, Cristina; Genazzani, Armando A.; Ribaldone, Davide Giuseppe (Frontiers in Medicine, 2023)
Background Nicotinamide phosphoribosyltransferase (NAMPT) and nicotinic acid phosphoribosyl transferase (NAPRT) are key intracellular enzymes that participate in the biosynthesis on NAD but have also been shown to be released as proinflammatory cytokines. A number of reports have shown that circulating NAMPT is increased in serum of patients with inflammatory disorders, including inflammatory bowel diseases (IBD), while nothing is known regarding circulating NAPRT and the presence of both cytokines in IBD patient stools. In the present study, we evaluated eNAMPT and eNAPRT levels in a large cohort of IBD patients not on biological therapy and in a subset that then was prescribed biologics. Methods We conducted a retro-perspective study on 180 patients, of which 111 underwent subsequent biological treatment (adalimumab, vedolizumab, and ustekinumab). We analyzed eNAMPT and eNAPRT concentrations in serum and faces of IBD patients, correlating them with response to biologics. Results We now report that eNAMPT and eNAPRT are significantly increased in both serum and stools of IBD patients. NAMPT and NAPRT levels correlate with disease severity, with C reactive protein and with serum IL-6 levels. Importantly, levels of NAMPT in patients starting treatment with adalimumab correlate with response failure at three months: patients with levels above 4 ng/ml were significantly less likely to obtain benefit. Serum NAMPT as a biomarker of response yields a sensitivity of 91% and a specificity of 100%. Conclusion The present work strongly suggests that a prospective trial evaluating eNAMPT and eNAPRT levels in relation to response to biologicals in IBD should be initiated.